EDUCATION AND TRAINING Ten reasons why every junior doctor should spend time working in a remote and rural hospital. Issue 1 (2020) - Fox, Kevin; Corstorphine, Wendy; Frazer, Jenny; Johnstone, Anna; Miller, Alasdair; Shepherd, Neil; Cooper, Paul
No abstract available